Influence of Learning Model Team Games Tournament on Learning Results IPAS Materials on Changes in the Form of Objects in grade IV students of SDN 4 Karang Anyar - Yanti, Catur; Herpratiwi, Herpratiwi; Nureva, Nureva (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The aim of this study was to identify the effect of the Team Games Tournament learning model on the learning outcomes of IPAS material on Changes in the Form of Objects in grade IV students of SD Negeri 4 Karang Anyar. This type of quantitative research was used in this study with a one group pre-test and posttest pre-experiment approach. The population was 30 students and a sample of 30 students or a saturated sample. Data collection techniques with multiple choice tests totaling 20 questions. The author conducted a validity test, then a reliability test, then a difficulty test, then a differentiation test and an error analysis test before the instrument was given to students. The method for analyzing data uses homogeneity, normality and hypothesis tests with paired t-tests. This study indicates that the Team Games Tournament learning model has an influence on IPAS learning outcomes, with an average pretest of 59.33 and posttest of 79.16. The results of the hypothesis test t_hitung 17.448> t_table, 1.699 with a Sig. (2-tailed) value of 0.000 <0.05 then H_a is accepted and H_o is rejected. Based on that, it means that there is an influence of the Team Games Tournament (TGT) Learning Model on the Learning Outcomes of IPAS Material Changes in the Form of Objects of Fourth Grade Students of SD Negeri 4 Karang Anyar.